2020
DOI: 10.1002/smtd.202000928
|View full text |Cite
|
Sign up to set email alerts
|

Flame Synthesized Blue TiO2−x with Tunable Oxygen Vacancies from Surface to Grain Boundary to Bulk

Abstract: Fabrication of nonstoichiometric metal oxides containing oxygen vacancies (OVs) has been an effective strategy to modulate their (photo)catalytic or (photo)electrochemical performances which are all affected by charge transfer at the interface and in the bulk. Considerable efforts are still needed to achieve tunability of OVs, as well as their quantitative characterization. Herein, a one‐step flame synthesis method is reported for the first time for fast fabrication of blue TiO2−x with controllable defect cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 61 publications
1
44
0
Order By: Relevance
“…S9b † XPS analysis was conducted to analyze the chemical valence of Pt and Pb after the photoreactions. Since metallic Pt 0 is regarded as the active site for photocatalytic H 2 generation, 45 its percentage in the Pt species will largely affect the photocatalytic activity. As shown in Fig.…”
Section: Photo-deposition Of Pt/pbo 2 On Cs/cn-ii and Cs/cn-zmentioning
confidence: 99%
“…S9b † XPS analysis was conducted to analyze the chemical valence of Pt and Pb after the photoreactions. Since metallic Pt 0 is regarded as the active site for photocatalytic H 2 generation, 45 its percentage in the Pt species will largely affect the photocatalytic activity. As shown in Fig.…”
Section: Photo-deposition Of Pt/pbo 2 On Cs/cn-ii and Cs/cn-zmentioning
confidence: 99%
“…Furthermore, at values of φ larger than one, the intermediate species in the formation pathway of NPs are identified as oxygen deficient. Consequently, the particles at the end of the synthesis have a high concentration of oxygen vacancies (OVs), resulting in amorphous structures [ 55 ].…”
Section: Effect Of Operation Conditions In Combustionmentioning
confidence: 99%
“…Wu and coworkers reported the fabrication of TiO 2− x with controllable oxygen vacancies by varying the deposition time of the samples on the substrate. 144 EPR studies demonstrated that the signal at g = 1.93 signified the existence of Ti 3+ in TiO 2− x . Almost no signal was observed with prolonged exposure to air during the deposition, which was attributed to the Ti 3+ oxidized to Ti 4+ .…”
Section: Strategies For Defect Engineeringmentioning
confidence: 99%